2015
DOI: 10.1159/000441046
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and Molecular Findings in Children with Acute Lymphoblastic Leukemia: Experience of a Single Institution in Argentina

Abstract: The purpose of the current study was to evaluate the cytogenetic findings in 1,057 children with acute lymphoblastic leukemia (ALL) referred to the cytogenetics laboratory at the Hospital de Pediatría Dr. Juan P. Garrahan, between 1991 and 2014. Chromosomal abnormalities were evaluated by G-banding and FISH. Since December 2002, RT-PCR determinations were systematically carried out for BCR-ABL1, KMT2A-AFF1, ETV6-RUNX1, and TCF3-PBX1 rearrangements in children, adding KMT2A-MLLT3 and KMT2A-MLLT1 in infants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
1
10
0
6
Order By: Relevance
“…In the present study, unlike the numerical abnormalities, the structural tended to be random which goes in agreement with that previously reported 2,7,19 . We detected dup(1q) in 15% of c‐HeH patients, and this goes in concordance with previous studies 20‐22 that reported dup (1q) to be present in about 10‐15% of HeH cases.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, unlike the numerical abnormalities, the structural tended to be random which goes in agreement with that previously reported 2,7,19 . We detected dup(1q) in 15% of c‐HeH patients, and this goes in concordance with previous studies 20‐22 that reported dup (1q) to be present in about 10‐15% of HeH cases.…”
Section: Discussionsupporting
confidence: 93%
“…Cytogenetic analysis has become a very useful method to determine acquired chromosomal abnormalities in the diagnosis of leukemia. The chromosomal abnormality rate varies from 47.3% to 89% in different studies, depending on the number of patients enrolled with ALL . BL was first described by Burkitt in 1958 as an aggressive lymphoma .…”
Section: Discussionmentioning
confidence: 99%
“…Out of these 12 genes, EGFL7 , CALN1 , TUSC3 and TNFRSF21 were the top genes that were found to be highly expressed (>2 log fold change) in ETV6-RUNX1 positive group in comparison to MLL and E2A-PBX1 positive groups as well as were bound strongly by IGF2BP1 from the eCLIP dataset. CALN1 has previously known to be overexpressed in ETV6-RUNX1 leukemia but its exact function is still unknown ( 38 ), while TUSC3 is reported to be a tumor suppressor gene ( 39 ). Among these gene, EGFL7 has been shown to play a role previously in the pathogenesis of Acute Myeloid Leukemia (AML) and hematopoiesis and is also known to be overexpressed in ETV6-RUNX1 leukemia ( 40 , 41 ).…”
Section: Resultsmentioning
confidence: 99%